The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2016gl069481
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of solar wind control on Jovian UV auroral activity deciphered by long‐term Hisaki EXCEED observations: Evidence of preconditioning of the magnetosphere?

Abstract: While the Jovian magnetosphere is known to have the internal source for its activity, it is reported to be under the influence of the solar wind as well. Here we report the statistical relationship between the total power of the Jovian ultraviolet aurora and the solar wind properties found from long‐term monitoring by the spectrometer EXCEED (Extreme Ultraviolet Spectroscope for Exospheric Dynamics) on board the Hisaki satellite. Superposed epoch analysis indicates that auroral total power increases when an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 36 publications
3
39
2
Order By: Relevance
“…Superposed epoch analysis might be effective. Kita et al (2016) reported positive correlation between the auroral power and duration of the quiescent interval of SW during the period of DOY −10 to DOY 50. After DOY 50, two cases on DOY 66 and 87 are predicted with quiescent intervals longer than 5 days.…”
Section: +mentioning
confidence: 96%
“…Superposed epoch analysis might be effective. Kita et al (2016) reported positive correlation between the auroral power and duration of the quiescent interval of SW during the period of DOY −10 to DOY 50. After DOY 50, two cases on DOY 66 and 87 are predicted with quiescent intervals longer than 5 days.…”
Section: +mentioning
confidence: 96%
“…Uncertainty in the arrival time of the solar wind shock structures, the Corotating Interaction Region and Coronal Mass Ejections, at Jupiter is dependent on the Earth‐Sun‐Jupiter angle, which was 82°–180° for the present analysis period. The arrival time uncertainty is estimated to be approximately a few days or more, as discussed in Kimura et al (, ), Kita et al (), and Tao et al (, ).…”
Section: Data Setmentioning
confidence: 97%
“…Uncertainties in propagated parameters for both models increase with Earth‐Sun‐Jupiter angle. Here this angle is between 17° (on 14 April) and 24° (on 24 April), so that solar wind extrapolations from this period should have a relatively high accuracy for both models (i.e., better than 20 h for shock arrival predictions and uncertainties <38% in maximum pressure values) [ Tao et al , ; Kita et al , ].…”
Section: Datamentioning
confidence: 99%